FEASTS Combined with Interferometry. III. The Low Column Density H i Around M51 and Possibility of Turbulent-mixing Gas Accretion - Xuchen Lin; Jing Wang; Lister Staveley-Smith; Suoqing Ji; Dong Yang; Xinkai Chen; Fabian Walter; Hsiao-Wen Chen; Luis C. Ho; Peng Jiang; Nir Mandelker; Se-Heon Oh; et al. (The Astrophysical Journal)
With a new joint-deconvolution pipeline, we combine the single-dish and interferometric atomic hydrogen (H i ) data of M51 observed by the Five-hundred-meter Aperture Spherical radio Telescope (FAST) (FEASTS program) and the Very Large Array (VLA) (THINGS). The product data cube has a typical line width of 13 km s ^−1 and a 2 σ line-of-sight (LOS) sensitivity of H i column density N _H _i ∼ 3.2 × 18 cm ^−2 at a spatial resolution of ∼18″ (∼0.7 kpc). Among the H i detected LOSs extending to ∼50 kpc, ∼89% consist of diffuse H i only, which is missed by previous VLA observations. The distribution of dense H i is reproduced by previous hydrodynamical simulations of this system, but the diffuse component is not, likely due to unresolved physics related to the interaction between the circumgalactic and interstellar media. With simple models, we find that these low N _H _i structures could survive the background ultraviolet photoionization, but are susceptible to the thermal evaporation. We find a positive correlation between LOS velocity dispersion ( σ _v ) and N _H _i with a logarithmic index of ∼0.5. Based on existing turbulent mixing layer (TML) theories and simulations, we propose a scenario of hot gas cooling and accreting onto the disk through a TML, which could reproduce the observed power index of ∼0.5. We estimate the related cooling and accretion rates to be roughly one-third to two-thirds of the star formation rate. A typical column density of diffuse H i (∼10 ^19 cm ^−2 ) can be accreted within 300 Myr, the interaction timescale previously estimated for the system. Such a gas accretion channel has been overlooked before, and may be important for gas-rich interacting systems and for high-redshift galaxy evolution.